ANALISIS PRODUK EFEK BERAGUNAN ASET SYARIAH DAN PERBANDINGANNYA DENGAN KONVENSIONAL - Nur Faizin Muhith; Aryo Prakoso; Nur Anisah; Husnul Hatimah (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
This article is a literature review that aims to describe, explain, and answer in more detail the problems of conventional Asset-Backed Securities (ABS) and compare them with sharia ABSs. From the results of the literature review, it is known that conventional ABS and sharia ABS are not much different in concept. Sharia ABS in its issuance is still based on sharia principles. Furthermore, there are two sharia ABSs, namely Collective Counter Investment (CCI), the second ABS issued by asset financial institutions. The difference between the two lies in the issuer and the assets that form the basis of the Islamic Securities issuer. The result of this paper is that it can increase literacy, especially in asset-backed securities products, and provide direction for further research.